2014
DOI: 10.1002/stem.1533
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of Juvenile, but not Adult, Mammary Gland Increases Stem Cell Self-Renewal and Estrogen Receptor Negative Tumors

Abstract: Children exposed to ionizing radiation have a substantially greater breast cancer risk than adults; the mechanism for this strong age dependence is not known. Here we show that pubertal murine mammary glands exposed to sparsely or densely ionizing radiation exhibit enrichment of mammary stem cell and Notch pathways, increased mammary repopulating activity indicative of more stem cells, and propensity to develop estrogen receptor (ER) negative tumors thought to arise from stem cells. We developed a mammary line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 50 publications
(88 reference statements)
1
52
0
Order By: Relevance
“…Genes decreased in MaSC signature were also decreased in K18-IHPsi (P ¼ 7 Â 10 À5 ), consistent with their ER-negative status, and likely reflecting the MaSC as cell of origin (36). This signature was not evident in K14/18-IHPsi, suggesting that host irradiation has tumorspecific engagement ( Supplementary Fig.…”
Section: Z-scorementioning
confidence: 53%
See 1 more Smart Citation
“…Genes decreased in MaSC signature were also decreased in K18-IHPsi (P ¼ 7 Â 10 À5 ), consistent with their ER-negative status, and likely reflecting the MaSC as cell of origin (36). This signature was not evident in K14/18-IHPsi, suggesting that host irradiation has tumorspecific engagement ( Supplementary Fig.…”
Section: Z-scorementioning
confidence: 53%
“…Our prior studies show that irradiating hosts with either sparsely or densely ionizing radiation shifted the dominant tumor type from ER-positive to ER-negative (30,36). Most (62%, n ¼ 15/24) tumors arising in sham-irradiated mice were ER-positive, compared with 33% (n ¼ 4/12) in g-irradiated hosts and 43% (n ¼ 15/35) in Si-irradiated (combined dose groups) hosts.…”
Section: Resultsmentioning
confidence: 96%
“…The tumor growth rate of tumors arising from transplantation to adults was comparable to that observed in previous experiments(23). Moreover the difference of tumor growth rate was replicated in cohort of mice transplanted as adults versus juveniles in an independent study(28). Mitotic figures that included the spectrum of condensed chromosome states (Figure 2B) were quantified in high-powered fields of view (n=10) per hematoxylin and eosin (H&E)-stained tumor.…”
Section: Resultsmentioning
confidence: 95%
“…It was shown that pubertal murine mammary glands exposed to sparsely or densely ionizing radiation transiently increased stem cell self-renewal that increased susceptibility to developing ER-negative breast cancer [247]. An exposure of six to eight week old female mouse to a clinically relevant radiation dose (2 Gy of whole body γ-radiation) caused longterm activation of mammary gland genes involved in proliferative and metabolic pathways, which are known to have roles in carcinogenesis [248], and a study which evaluated mammary carcinogenesis initiated by combined exposure to various doses of γ-radiation and chemical carcinogens (1-methyl-1-nitrosourea or 1-methyl-6-phenyl-1H-imidazo [4,5-b]pyridin-2-amine), using a rat model and molecular biological approaches, provided evidence of a multilevel interaction: a synergistic interaction between radiation and a chemical carcinogen at the initiation level and an additive interaction in the incidence of resulting carcinomas [249].…”
Section: Ionizing Radiationmentioning
confidence: 99%